ORAL PHENAZOPYRIDINE HCL FOR URETER ORIFICE IDENTIFICATION AND RETROGRADE STENTING - Gumilar, Ogi Bahaurini; Soebadi, Doddy M; Djojodimedjo, Tarmono; Askandar, Brahmana; Pudjirahardjo, Widodo J (Indonesian Journal of Urology, 2015)
Objective:  To compare the successful of the identification of the ureteral orifice at cervical cancer patients who received phenazopyridine orally and to analyze the correlation between hydronephrosis and successful rate for retrograde stenting. Material & Method: This was a comparative experimental study, using phenazopyridine hcl orally prior to cystoscopy to identify the ureteral orifice on cervical cancer patients and to perform retrograde stenting on spotted ureteral orifice. Forty samples provided consent to enroll in this study. Mean age was 49.2 ± 5.16 years. Thirty-four out of 40 samples was confirmed as squamous cell carcinoma type. Results: Chi-square test demonstrated no significant differentiation in finding ureteral orifice between treatment and control group on stage 3B (p = 0.408). However, result shown conversely on stage 4A (p = 0.046). There was no significant disparity in conducting retrograde stenting between treatment and control group on stage 2B and 3B (p = 0.221 and p = 0.197). There was no significant correlation between hydronephrosis gradation and retrograde stenting on control group (p = 0.144). Conclusion: Administration of phenazopyridine HCL orally in cervical cancer patients increase success for ureteral orifice identification and retrograde stenting, but not statistically significant. There is no correlation between hydronephrosis with a success retrograde stenting.Keywords: Cervical cancer, hydronephrosis, phenazopyridine hcl, ureteral orifice, retrograde stenting.